ROTOTIPE PENDETEKSI KANDUNGAN ZAT METANA UNTUK PEMBUDIDAYAAN JAMUR TIRAM BERBASIS MIKROKONTROLLER ARDUINO - Diah Aryani; Fanida Yantiar; Muhammad Husni Farid (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Oyster mushroom (Pleurotus ostreatus) is an edible mushroom from the group Basidiomycota and including Homobasidiomycetes class with common characteristics of fruit grown white to beige and hood berbebtuk semicircle similar to oyster shells with the middle aga jekung .Jamur oyster is still a relative with Pleurotus eryngii and commonly known as oyster kingh Mushoom. Many farmers are still having trouble oyster mushrooms in oyster mushroom cultivation process itself. In addition to climatic factors and weather, the state of the environment can also affect the growth of oyster mushrooms. With the advancement in the field of communication and Arduino microcontroller today, the oyster mushroom farmers can use it as auxiliary media of oyster mushroom growth. With the aid of temperature sensors, soil moisture sensors and gas sensors MQ-2. Then it is no longer impossible. Soil conditions, weather temperature and methane content of substances contained in the soil, can bemonitored through a single device. So that this tool can help farmers in order to produce oyster mushroom oyster mushrooms with superior quality.